Flipped Classroom in Organic Chemistry Has Significant Effect on Students’ Grades - Cormier, Caroline; Voisard, Bruno (Frontiers in ICT, 2018)
The flipped classroom as a form of active pedagogy in post-secondary chemistry has been developed during the last 10 years and has been gaining popularity with instructors and students ever since. In the current paradigm in STEM (science, technology, engineering and mathematics) education, it is widely recognized that active learning has significant positive effects on students’ grades. Post-secondary organic chemistry is a difficult course for students and the traditional way of teaching does not foster students’ active involvement. Implementation of active pedagogy could increase students’ achievement in this course. However, few quantitative data are available on the impact of active pedagogy in general, or flipped classrooms in particular, on learning in organic chemistry at a post-secondary level. Thus, in the present study, we evaluated the gain on final grade scores in organic chemistry after implementing a flipped classroom approach to promote active learning in this course. We encouraged students to be active by having them watch educational videos prior to each class and then having them work during class time on problems that focused on applying the concepts presented in the videos. Exams were the same as those completed by students in the traditional classrooms of our college. In an a posteriori analysis of our students’ grades, we compared final grades in traditional classrooms (control group, N = 66) and in flipped classrooms (experimental group, N = 151). The sample was stratified in three categories depending on students’ academic ability in college, from low-achieving to high-achieving students. Our results show that students in the experimental group have significantly higher final grades in organic chemistry than those in the control group, that is 77% for students in the active classroom vs. 73% in the traditional classroom (p < 0.05). The effect was the greatest for low-achieving students, with final scores of 70% in the active classroom compared to 60% in the traditional one (p < 0.001). This difference in performance is likely due to students spending more time solving problems in a flipped classroom rather than having the questions assigned to them as homework.